Analisis Strategi Pemasaran Agribisnis Bawang Goreng dalam Meningkatkan Volume Penjualan (Studi Kasus Rumah Produksi Raka La Rangga di Kabupaten Dompu) - Dudy Achdiat Katamsih; Chairul Adhim; Fahrul Mauzu (Jurnal Strategi dan Inovasi Bisnis, 2026)
Background: The Raka La Rangga fried onion MSME in Dompu Regency has high-quality products, yet its sales remain unstable due to weather-induced supply fluctuations, fierce competition, limited local distribution, and minimal digital promotion. This phenomenon highlights an integration gap in upstream-downstream studies on agribusiness MSMEs within production center areas. Purpose: This study aims to analyze the current marketing strategy and identify the determining factors influencing it. Methods: A descriptive qualitative approach was used with purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, then analyzed interactively covering data reduction, data display, and drawing conclusions. Results: The marketing strategy remains traditional, based on the 4P mix (local retail consignment and cost-based pricing) as well as personal online promotion. Challenges such as external competitors, high shipping costs, and unstable shallot prices are mitigated through a bulk stocking system. Conclusion: The implementation of the 4P strategy is not yet optimal in boosting sales due to distribution isolation and minimal digitalization. The determining factors include market competition, e-commerce competency gaps, and upstream supply chain vulnerabilities.